Powder Bed Fusion Techniques in Metal 3D Printing: A Review - Rasool, Inayat; Afzal, Mohammad; Khan, Rehbar; Khan, Ateeb Ahmad (Applied mechanics and materials, 2024)
The use of 3D printing (additive manufacturing) with metal has grown significantly in demand recently, greatly reducing the time and expense required to produce complex interconnected metal components. This method minimizes material wastage, facilitates material recycling, and eliminates the need for support materials. Among the various Metal Additive Manufacturing techniques, Powder Bed Fusion (PBF) processes stands out as the most prevalent for manufacturing parts. Within the realm of PBF, electron beam melting technique, selective laser sintering technique, and selective laser melting technique are the primary methods employed. Selective laser melting and selective laser sintering operate without the need for any special conditions, unlike EBM, which necessitates a vacuum environment. Regarding the choice of materials, laser melting/sintering processes are suitable for almost all types of metals except those which surpasses beam melting capabilities. While electron beam melting is constrained to a few materials such as titanium alloys, cobalt and chromium alloys, and nickel alloys, whereas selective laser melting and sintering allows for a broad range of materials, including iron and steel alloys. However, electron beam melting exhibit the ability to process brittle materials that would typically be challenging for melting and sintering through laser. Nevertheless, the ductility, yield testing, and ultimate testing of materials created through EBM are inferior to those processed by laser methods. Although all PBF techniques excel at creating complex structures, finishing products to have a smooth surface directly over a rough surface remains a subject of ongoing research. To attain suitable mechanical properties such as hardness, tensile strength, and endurance, critical process factors include power of laser or beam, speed for scanning, density for powder bed, thickness of laser or beam, and material characteristics. Inadequate material selection coupled with incorrect process settings can lead to issues such as porosity, slag formation, and other flaws.